THE INFLUENCE OF TEACHER PERFORMANCE APPRAISAL ON LEARNING INNOVATION IN THE DIGITAL ERA - Fani Yustiadi; Moh Syaifuddin; Arif Budi Wurianto (Prima Magistra: Jurnal Ilmiah Kependidikan, 2025)
Teacher Performance Appraisal plays an important role in enhancing the quality of learning, especially in vocational hingh schools where innovation is crucial to meet the challenges of the digital era. However, empirical evidence on the relationship between Teacher Performance Appraisal and teachers’ learning innovation is still limited. This study employed a quantitative approach with a survey method. Data were collected from 75 Private Vocational High Schools that are members of the Head Teacher's Working Group Banyuwangi Region 3 (Genteng, Glenmore, and Sempu) using an online Likert-scale questionnaire. Data were analyzed using descriptive statistics and simple linear regression with SPSS 25.0. The results indicate that both Teacher Performance Appraisal and learning innovation levels are in the “Good” category. Regression analysis shows a positive and significant relationship between Teacher Performance Appraisal and learning innovation, with a significance value of 0.000 (<0.05) and a coefficient of determination (R²) of 0.521. This implies that 52.1% of the variance in learning innovation is explained by Teacher Performance Appraisal. The findings suggest that Teacher Performance Appraisal contributes significantly to motivating teachers to adopt innovative teaching practices. This highlights the importance of optimizing Teacher Performance Appraisal implementation not only as an evaluative tool but also as a strategic instrument for continuous professional development in vocational education.